Mineralogia e geoquímica dos depósitos de fosfatos aluminosos lateríticos da região Bonito-Ourém, no Estado do Pará - QUEIROZ, Alan Felipe dos Santos (Universidade Federal do Pará, 2022)
Recent research carried out in the Bonito-Ourém region provided the discovery of four new targets, called Caeté, Tracuá, Serrote and Serrotinho, whose preliminary chemical composition evaluation indicated an economic potential for phosphorus, like the Bonito phosphate deposit. However, new specifications and chemical studies involving stoichiometric calculations were carried out and pointed to mineralogical variations in two of the four targets in relation to the Bonito deposit mineralogy, mainly crandallitic. The main objective of this present study is to investigate the geology, mineralogy, and geochemistry of these new deposits, aiming to identify possible variations of these deposits with those of the Bonito deposit and of the Gurupi region, in addition to investigating whether these deposits would fit the genetic model of the great majority of aluminum phosphate deposits in the Northeast of Pará and Northwest of Maranhão. The methodology consisted of a technical visit, description of cores and sample collection, followed by analytical/laboratory activities, such as optical microscopy, x-ray diffraction and whole rock chemical analysis. In general, the targets Serrotinho, Serrote, Tracuá and Caeté are small and isolated hills, with altitudes ranging from 50 to 90 m. They were developed over mature lateritic formations, complete and/or truncated, with at least one horizon enriched in aluminum phosphates. The profiles have a maximum thickness of 9 m and are often structured in four horizons, composed from the base to the top by a saprolitic horizon, a clayey horizon, an aluminous phosphatic horizon and a ferroaluminous phosphatic horizon. The mineralogy and distribution of minerals in the profiles are horizon-dependent and very similar among the investigated profiles. In Serrotinho and Serrote, the predominant phosphates are crandallite-goyazite-woodhouseite-svanbergite and wardite, while in Tracuá and Caeté augelite predominates and only in Caeté the presence of variscite was observed. In addition to augelite, gibbsite compose the main mineralogy of the phosphate aluminous crust of Tracuá and Caeté profiles. From the results, it turns out that the Serrotinho, Serrote, Tracuá and Caeté deposits have many similarities with each other and with the deposits and occurrences of lateritic phosphates in the Gurupi region, especially with Sapucaia and Boa Vista. It is understood that Sapucaia, Boa Vista, Serrotinho and Serrote derived from a similar aluminosilicate sequence, while Tracuá and Caeté may have been developed on phosphate-enriched metasedimentary sequences, similar to the Pirocaua and Cansa Perna deposits in the Gurupi Belt region.